Time-varying lifestyle and mental-ill health risk factors for the longitudinal development of daily activity limitations among middle-aged and older adults in Thailand - Dararatt Anantanasuwong; Supa Pengpid; Karl Peltzer (Translational Medicine of Aging)
The aim of this study was to assess the longitudinal association between lifestyle factors, mental ill-health indicators and activities of daily living (ADL) disability among ageing adults in Thailand. We analyzed the cohort data of participants (5616 in 2015, 3600 in 2017 and 2863 in 2020) over the age of 45 from three consecutive waves of HART (health, age, retirement) in Thailand. ADL disability was assessed with a 4-item ADL scale. In order to evaluate the longitudinal correlation between measurement of lifestyle factors, mental health indicators, and ADL disability between three survey waves, we conducted a Generalized Estimate Equation Analysis (GEE). The proportion of ADL disability increased from 3.8 % in 2015 to 7.0 % in 2020. In the final GEE logistic regression model, adjusted for various confounding factors, probable depression (aOR: 1.95, 95 % CI: 1.47–2.59), self-reported poor mental health (aOR: 1.28, 95 % CI: 1.45–2.27), poor quality of life/happiness (aOR: 1.28, 95 % CI: 1.03–1.61), loneliness (aOR: 1.66, 95 % CI: 1.33–2.08), brain disease/dementia (aOR: 4.84, 95 % CI: 2.70–8.67), physical inactivity (aOR: 6.91, 95 % CI: 4.41–10.84) and having underweight (AOR: 1.33, 95 % CI: 1.00–1.76) were positively associated with ADL disability. Current smoking (aOR: 0.39, 95 % CI: 0.24–0.64) was negatively associated with ADL disability.We found that lifestyle factors (physical inactivity and having underweight) and loneliness, poor quality of life/happiness, probable depression, self-reported poor mental health, and brain disease/dementia were associated with ADL disability. Enhancing lifestyle factors relating to physical activity and healthy diet, and screening and treatment of mental ill-health indicators may reduce ADL disability in Thailand.